COGNITIVE PSYCHOLOGY STUDY AND MATHEMATICAL PROCESS SKILLS ON STUDENTS' ANSWERS IN MATHEMATICS LEARNING IN COMPARATIVE MATERIAL - Kamid, Kamid; Ramalisa, Yelli; Rohati, Rohati; Ningsih, Rita; Nabilah, Balqis Saffanah (LPPM Universitas Jambi, 2024)
This research explores the differences between the two schools regarding three key variables: students' cognitive psychology, mathematical processing skills, and responses to mathematics learning, specifically within the context of comparative material in Grade VII. Additionally, it seeks to compare these three variables to understand how they vary across the two institutions. The study adopts a quantitative approach, with purposive sampling used to select a sample of 120 Grade VII students from two junior high schools. Data were gathered using a questionnaire based on a Likert scale, and analysis was conducted using comparison tests through specialized data processing software. The results revealed significant differences in students' cognitive psychology, mathematical processing skills, and responses to mathematics learning between the two schools. These variations suggest underlying factors related to the learning environment, teaching strategies, or institutional differences that influence student performance and engagement in mathematics. What sets this study apart is its comprehensive comparison of cognitive and skill-based factors in mathematics learning across different school settings. Unlike previous research that examines these variables in isolation, this study integrates cognitive psychology and mathematical processing skills with student feedback, providing a holistic view of the learning experience. Doing so offers more profound insights into how school-specific conditions can shape students’ cognitive and mathematical abilities, thereby informing more tailored educational strategies to improve mathematics learning outcomes across diverse educational contexts.